Desenvolvimento e validação de uma escala para avaliação de integração do LCMS no processo formativo no Ensino Superior - Ferreira, Sérgio André (2014)
Considering the importance of the management of Learning Content Management System (LCMS) in pedagogical strategy of higher education modernisation, it becomes essential to develop tools, reliable and adapted to the context, to collect students ' perceptions on the issue. Additionally, it is important that this information may be linked to other sources, in particular, with the reports of LCMS, in such a way as to promote a more coherent management. The purpose of this study is to develop and validate the scale "LCMS integration in teaching activities of higher education". The methodological approach to the subject has developed along three steps: 1- Identification and development of the dimensions and writing of individual items; 2-Validation of the content of the instrument by a panel of experts and graduate students with deep experience in the use of the LCMS; 3-Administration of scale and psychometric analysis. The dimensions of the final version of the scale are related very closely with information from reports of LCMS. The objective is to analyze, crossing information from two sources, a factor which potentially increases management effectiveness. It was constituted a convenience sample of 54 students attending undergraduate and master's Universidade Católica do Porto. The results suggest that the scale has good psychometric properties.